Murphy, Russ. Interview about broadcasting and radio history. - Murphy, Russ. (2019)
Russ Murphy talks about broadcasting and radio history, various radio stations, music and recording artists, sports and soccer, and changes to the radio industry over time. "00:00: Russ Murphy, September 25, 2019, 76 years old, Marystown; 00:59:1962, CHCM, remote communities, two job offers, President Kennedy, instrumental music; 04:45: household radio, father, Michael Murphy, country and western, Don Messer; 05:53: 1940’s, VOCM, VONF, Ayre and Sons, churches, private stations; 06:45: 1936, Joe Butler, Walter Williams, call signs; 07:36: VOCM system, January, 2018; 08:06: Argentia, freight shed, islands, communities, Placentia Bay; 09:27: Austin Pike, wharf, Marystown, future wife, Margaret;09:55: 1964, Charlie Noseworthy, manager, Don Hollett, sales, Maggie Drake, receptionist, Geraldine Kelly, office and music library, announcers, Walt Forsey, Pat Murphy, Mick Stoxkley, George McLaren, three announcers left, new hires,Russ Murphy, Don Thistle, Ed Pike; 10:51; popular shows and theme music; 11:58; Charlie Noseworthy, mentor, great team leader; 12:17; 1966, transfer, VOCM, St John’s, Competition, CJON; 13:45: producer, VOCM phone show, Bill Williamson, Ron Pumphrey; 14:16: 1971, station manager, Marystown, detailed “tour” of radio station, CHCM; 20:59: music, library, formats, recording artists, local favourites; 26:25: listening audience, remote broadcasts, St Pierre and Miquelon, BBM statistics; 28:56: staff involvement in community;30;14; contests, promotions, radio bingo. Christmas Turkey Show; 31:50: renown, recognition, community support, accolades, recognition, small station, big agenda, big results; VOCM/CHCM 10k road race; 35:12: former employees, various achievements, celebrities, Ron Hynes, John Furlong, Jim Wellman, George McLaren, Don Hollett; 36:37: Russ Murphy interviews, singers, politicians, community events, cod filleting contest, Marystown Agricultural Craft Fair and Exhibition, live broadcast, listener hearing own voice for first time, Bas Jamieson, shipyard, fish plant, Marystown Mall, ...